Fiber material with annular fold structure as well as preparation method and application of fiber material

By using composite fiber material with annular wrinkle structure in wound dressings, combined with electrospinning and heat treatment technology, the problem of poor mechanical properties of existing dressings in wounds in large deformation areas is solved, and excellent anti-top breaking and elastic recovery performance is achieved.

CN119746130APending Publication Date: 2025-04-04DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411839876.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing wound dressings have poor mechanical properties on wounds in large deformation areas, which can easily lead to structural damage and functional failure during movement, especially in joints with frequent apex.

Method used

Using composite fiber material with an annular pleated structure, the natural polymer/PCL fiber membrane layer is composited with the heat-shrinkable material fiber membrane layer through electrospinning technology, and a ring-shaped pleated structure is formed by heat treatment.

Benefits of technology

When the material is subjected to a blasting force, it can be deployed in the direction of the force and returns to its initial state after the force is removed, which significantly improves the anti-blasting performance and elastic recovery ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746130A_ABST
    Figure CN119746130A_ABST
Patent Text Reader

Abstract

The invention relates to a fiber material with an annular fold structure as well as a preparation method and application thereof. The fiber material comprises a natural high-molecular polymer / polycaprolactone (PCL) fiber membrane layer and a thermal shrinkage material fiber membrane layer, wherein the composite fiber material has an annular wrinkle structure. The bursting resistance of the dressing can be greatly improved, the service life is prolonged, and the medical dressing has a wide application prospect in the field of medical dressings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedicine, and particularly relates to a fiber material with an annular fold structure, a preparation method and an application thereof. Background Art

[0002] Traumatized skin is easily invaded by bacteria, which can even be life-threatening in severe cases. Wound dressings can protect wounds and prevent bacterial infection. Electrospun fiber materials have become one of the most promising wound dressings because their nanofiber structure can simulate the natural extracellular matrix structure, which is beneficial to cell adhesion and growth. However, for wounds in large deformation areas, the mechanical properties of the dressings are poor, which can easily lead to structural damage and functional failure during movement. Especially in areas such as finger joints and elbow joints, frequent bursting behavior puts higher requirements on the anti-bursting ability of the dressing, and it is urgent to develop dressings with excellent anti-bursting ability and elastic recovery ability. Summary of the invention

[0003] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a fiber material with an annular pleated structure and a preparation method and application thereof.

[0004] The present invention provides a composite fiber material, characterized in that the composite fiber material comprises a natural high molecular polymer / PCL fiber membrane layer and a heat shrinkable material fiber membrane layer; wherein the composite fiber material has an annular pleated structure.

[0005] Furthermore, the natural high molecular polymer / PCL fiber membrane side is the skin-contacting surface, and the heat-shrinkable material fibers are away from the skin-contacting surface.

[0006] Preferably, the thickness ratio of the natural polymer / PCL fiber membrane layer to the heat-shrinkable material fiber membrane layer is 0.2 to 0.8;

[0007] Preferably, the heat shrinkable material is one or more of PU and PLGA;

[0008] Preferably, the natural high molecular polymer includes one or more of gelatin and collagen;

[0009] Preferably, the annular folds have a wavelength of 50 to 300 μm and an amplitude of 15 to 60 μm.

[0010] Furthermore, the composite fiber membrane has a bursting strength of 3 to 10N and a bursting recovery rate of 70 to 100%.

[0011] The present invention provides a method for preparing a composite fiber material, comprising:

[0012] (1) mixing a natural polymer, PCL, and a solvent to obtain a spinning solution, electrospinning to obtain a polymer / PCL fiber membrane, and compounding the polymer / PCL fiber membrane on a heat-shrinkable material fiber membrane;

[0013] (2) Heat cross-linking and then place flat for heat treatment to obtain a composite fiber membrane.

[0014] Preferably, the natural high molecular polymer in step (1) includes one or more of gelatin and collagen; the heat shrinkable material in the heat shrinkable material fiber membrane includes one or more of PU and PLGA;

[0015] Preferably, in step (1), the mass ratio of the natural high molecular polymer to PCL is 3:1 to 1:3;

[0016] Preferably, the solvent in step (1) comprises one or more of hexafluoroisopropanol, dichloromethane, tetrahydrofuran, and acetic acid;

[0017] Preferably, the thickness of the heat-shrinkable fiber film in step (1) is 30 to 80 μm.

[0018] The thickness of the heat-shrinkable fiber membrane should not be too small or too large. If it is too small, the heat-shrinkable fiber membrane will not be able to shrink enough in hot water and cannot drive the upper natural polymer / PCL fiber membrane to fold; if it is too large, the heat-shrinkable fiber membrane will shrink too much in hot water, and the shrinkage rate of the upper and lower fiber membranes will be different, which will easily cause separation from the upper natural polymer / PCL fiber membrane.

[0019] Preferably, the mass percentage concentration of the spinning solution in step (1) is 5-20wt%, that is, the total mass fraction concentration of the natural polymer and PCL is 5-20wt%; the electrospinning process parameters in step (1) include: spinning voltage of 10-20kV, receiving distance of 10-30cm, perfusion speed of 0.1-5mL / h, temperature of 10-30°C, and relative humidity of 20-70%;

[0020] Preferably, the heat-shrinkable material fiber membrane in step (1) is a heat-shrinkable material electrospun membrane;

[0021] The preparation of the heat-shrinkable material electrospinning membrane comprises: dissolving the heat-shrinkable material in a solvent to obtain a precursor spinning solution, electrospinning, and forming a heat-shrinkable material fiber membrane.

[0022] Furthermore, in the preparation of the heat-shrinkable material electrospinning membrane, the mass percentage concentration of the heat-shrinkable material in the precursor spinning solution is 5 to 20 wt %; the electrospinning parameters are: spinning voltage is 10 to 35 kV, receiving distance is 10 to 30 cm, perfusion speed is 0.1 to 10 mL / h, temperature is 10 to 30°C, and relative humidity is 20 to 70%.

[0023] Preferably, in the step (1), the thickness of the high molecular polymer / PCL fiber membrane is 10 to 30 μm; and the thickness ratio of the natural high molecular polymer / PCL fiber membrane to the heat shrinkable material fiber membrane is 0.2 to 0.8.

[0024] The thickness ratio of the natural polymer / PCL fiber membrane to the heat shrinkable material fiber membrane should not be too small or too large. If it is too small, the shrinkage rate of the upper and lower fiber membranes will be different, which will easily lead to interlayer separation; if it is too large, the PU fiber membrane will not be able to drive the upper natural polymer / PCL fiber membrane to fold.

[0025] Preferably, in step (1), the heat-shrinkable material fiber membrane is used as a receiving device to directly receive and compound the high molecular polymer / PCL fiber membrane.

[0026] Preferably, the heating cross-linking temperature in step (2) is 55 to 75° C. and the time is 15 to 60 minutes;

[0027] By heating and cross-linking, PCL is melted to form welding points at the fiber overlap, which enhances the stability of the fiber structure. If the temperature is too high or the time is too long, the fiber will completely melt and lose its fiber morphology; if the temperature is too low or the time is too short, PCL will not melt and welding points will not be formed.

[0028] In the step (2), the fiber membrane after heating and cross-linking is cut into regular shapes or irregular shapes;

[0029] Furthermore, the shape includes one of a circle, a square, a pentagon, and a hexagon.

[0030] In the step (2), the temperature of the horizontal heat treatment is 15 to 45° C. and the time is 5 to 60 minutes.

[0031] The temperature of the flat heat treatment should not be too high or too low, and the time should not be too long or too short. If the temperature is too high or the time is too long, the fiber will be completely melted and lose its fiber morphology; if the temperature is too low or the time is too short, the wrinkles cannot be completely formed.

[0032] Preferably, the horizontal heat treatment in step (2) is performed by horizontally placing the product in hot water.

[0033] Further, the fiber membrane is placed flat in hot water, wherein the fiber membrane is immersed in the water.

[0034] The invention provides an application of the composite fiber material in the field of medical dressings.

[0035] The present invention utilizes a heat-shrinkable fiber membrane (such as a PU fiber membrane) and a non-heat-shrinkable natural polymer / PCL fiber membrane to compound through a layer-by-layer electrospinning method. Under the stimulation of hot water, the heat-shrinkable fiber membrane undergoes isotropic contraction, driving the upper natural polymer / PCL fiber membrane to form annular folds from the outside to the inside. When the annular folds are subjected to a bursting radial force, the folds will expand along the force direction. When the force is removed, the folds will return to their initial state, which is conducive to providing anti-bursting performance.

[0036] Beneficial Effects

[0037] (1) The preparation method of the fiber membrane dressing with an annular pleated structure of the present invention is simple and easy to operate.

[0038] (2) The fiber membrane dressing of the annular pleated structure of the present invention has an upper layer of natural high molecular polymer / PCL fiber with annular pleats, and a lower layer of heat-shrunk high elastic PU fiber. Since the pleated structure can be unfolded when stressed and return to the initial state when not stressed, the dressing can be endowed with excellent anti-bursting performance. Compared with the ordinary parallel pleated structure, the annular pleated structure of the present invention is more suitable for joints. It can resist frequent joint bending and recovery, has good fatigue resistance, and has a long service life, and has great application advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is an electron microscope image of the fiber membrane dressing with an annular pleated structure of the present invention. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0041] Materials: Polyurethane, anionic, viscosity 20-200mPa.s, purchased from Guangzhou Biheng Chemical Technology Co., Ltd.; anhydrous ethanol, specification AR (Shanghai test), ≥99.7%, purchased from Sinopharm Chemical Reagent Co., Ltd.; gelatin, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; PCL, Mn = 80000 ~ 100000, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; hexafluoroisopropanol, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0042] Bursting performance test: YG(B)026G-500 universal testing machine was used to perform bursting test on the composite fiber membrane sample with an annular pleated structure (circular, with a diameter of 12 mm), and the bursting rate was 10 mm / min.

[0043] Example 1

[0044] The preparation method of the fiber membrane dressing with an annular pleated structure comprises the following specific steps:

[0045] (1) PU was dissolved in ethanol at a concentration of 5 wt% to obtain a precursor spinning solution, and electrospinning was performed with the following spinning parameters: spinning voltage of 20 kV, receiving distance of 15 cm, perfusion speed of 3 mL / h, temperature of 25 ± 2 °C, and relative humidity of 50 ± 5%. A hard release paper was used as a receiving substrate to obtain a PU fiber film with a thickness of 50 μm;

[0046] (2) Gelatin and PCL were dissolved in hexafluoroisopropanol, with a gelatin to PCL mass fraction of 1:1 and a total concentration of 10 wt % to obtain a precursor spinning solution. The PU fiber membrane was used as a substrate for electrospinning to obtain a gelatin / PCL fiber membrane with a thickness of 25 μm. The spinning parameters were as follows: spinning voltage of 10 kV, receiving distance of 15 cm, perfusion speed of 2.5 mL / h, temperature of 25±2°C, and relative humidity of 50±5%.

[0047] (3) heating in an oven at 65°C for 60 min to crosslink and dry;

[0048] (4) Cut the composite fiber membrane into uniform circles, place the fiber membrane side downward in 35°C hot water for 15 minutes, and obtain a fiber membrane dressing with an annular pleated structure, such as Figure 1 shown.

[0049] The fiber membrane dressing with an annular fold structure finally obtained has a fold wavelength of 100-200 μm, an amplitude of 30-55 μm, a bursting strength of 5-7N, and a bursting elastic recovery rate of 80-90%.

[0050] Example 2

[0051] The preparation method of the fiber membrane dressing with an annular pleated structure comprises the following specific steps:

[0052] (1) PU was dissolved in ethanol at a concentration of 10 wt% to obtain a precursor spinning solution, and electrospinning was performed with the following spinning parameters: spinning voltage of 20 kV, receiving distance of 10 cm, perfusion speed of 2 mL / h, temperature of 25 ± 2 °C, and relative humidity of 50 ± 5%. A hard release paper was used as a receiving substrate to obtain a PU fiber membrane with a thickness of 60 μm;

[0053] (2) Collagen and PCL were dissolved in hexafluoroisopropanol, with a mass fraction of collagen and PCL of 1:2 and a total concentration of 8 wt % to obtain a precursor spinning solution. The PU fiber membrane was used as a substrate for electrospinning to obtain a collagen / PCL fiber membrane with a thickness of 30 μm. The spinning parameters were as follows: spinning voltage of 20 kV, receiving distance of 10 cm, perfusion speed of 1.5 mL / h, temperature of 25±2°C, and relative humidity of 50±5%.

[0054] (3) heating in an oven at 60°C for 60 min to crosslink and dry;

[0055] (4) The composite fiber membrane was cut into uniform squares, with the fiber membrane side facing downward, and placed flat in 25°C hot water for 30 minutes to obtain a fiber membrane dressing with an annular pleated structure.

[0056] The fiber membrane dressing with annular pleated structure finally obtained has a pleated wavelength of 150-250 μm, an amplitude of 20-30 μm, a bursting strength of 4-5N, and a bursting elastic recovery rate of 75-80%.

[0057] Example 3

[0058] The preparation method of the fiber membrane dressing with an annular pleated structure comprises the following specific steps:

[0059] (1) PU was dissolved in ethanol at a concentration of 5 w / v% to obtain a precursor spinning solution, and electrospinning was performed with the following spinning parameters: spinning voltage of 10 kV, receiving distance of 25 cm, perfusion speed of 1 mL / h, temperature of 25±2°C, and relative humidity of 50±5%. A hard release paper was used as a receiving substrate to obtain a PU fiber membrane with a thickness of 60 μm;

[0060] (2) Gelatin and PCL were dissolved in hexafluoroisopropanol, with a gelatin to PCL mass ratio of 3:1 and a total concentration of 20 wt % to obtain a precursor spinning solution. The PU fiber membrane was used as a substrate for electrospinning to obtain a gelatin / PCL fiber membrane with a thickness of 15 μm. The spinning parameters were as follows: spinning voltage of 30 kV, receiving distance of 30 cm, perfusion speed of 1.5 mL / h, temperature of 25±2°C, and relative humidity of 50±5%.

[0061] (3) heating in an oven at 65°C for 15 min to crosslink and dry;

[0062] (4) The composite fiber membrane was cut into uniform pentagons, and placed flat in 15°C hot water for 30 minutes with the fiber membrane side facing downward to obtain a fiber membrane dressing with an annular pleated structure.

[0063] The fiber membrane dressing with annular pleated structure finally obtained has a pleated wavelength of 200-300 μm, an amplitude of 15-20 μm, a bursting strength of 3-4N, and a bursting elastic recovery rate of 70-75%.

[0064] Example 4

[0065] The preparation method of the fiber membrane dressing with an annular pleated structure comprises the following specific steps:

[0066] (1) PU was dissolved in ethanol at a concentration of 5 wt% to obtain a precursor spinning solution, and electrospinning was performed with the following spinning parameters: spinning voltage of 25 kV, receiving distance of 15 cm, perfusion speed of 3 mL / h, temperature of 25 ± 2 °C, and relative humidity of 50 ± 5%. A hard release paper was used as a receiving substrate to obtain a PU fiber film with a thickness of 70 μm;

[0067] (2) Gelatin and PCL were dissolved in hexafluoroisopropanol, with a gelatin to PCL mass fraction of 1:1 and a total concentration of 8 wt % to obtain a precursor spinning solution. The PU fiber membrane was used as a substrate for electrospinning to obtain a gelatin / PCL fiber membrane with a thickness of 20 μm. The spinning parameters were as follows: spinning voltage of 10 kV, receiving distance of 15 cm, perfusion speed of 2 mL / h, temperature of 25±2°C, and relative humidity of 50±5%.

[0068] (3) heating in an oven at 65°C for 30 min to crosslink and dry;

[0069] (4) Cut the composite fiber membrane into uniform circles, place the fiber membrane side downward in 35°C hot water for 30 minutes, and obtain a fiber membrane dressing with an annular pleated structure.

[0070] The fiber membrane dressing with an annular pleated structure finally obtained has a pleated wavelength of 50-150 μm, an amplitude of 40-60 μm, a bursting strength of 6-8N, and a bursting elastic recovery rate of 90-95%.

Claims

1. A composite fiber material, characterized in that: The composite fiber material comprises a natural macromolecular polymer / polycaprolactone PCL fiber membrane layer and a heat-shrinkable material fiber membrane layer; The composite fiber material has a ring-shaped pleated structure.

2. The composite fiber material according to claim 1, characterized in that: The thickness ratio of the natural polymer / PCL fiber membrane layer to the heat shrinkable material fiber membrane layer is 0.2 to 0.8; The heat shrinkable material is one or more of polyurethane PU and polylactic acid-glycolic acid copolymer PLGA; The natural high molecular polymer includes one or more of gelatin and collagen; The wavelength of the annular folds is 50 to 300 μm, and the amplitude is 15 to 60 μm.

3. A method for preparing a composite fiber material, comprising: (1) mixing a natural polymer, PCL, and a solvent to obtain a spinning solution, electrospinning to obtain a polymer / PCL fiber membrane, and compounding the polymer / PCL fiber membrane on a heat-shrinkable material fiber membrane; (2) Heat cross-linking and then place flat for heat treatment to obtain a composite fiber membrane.

4. The preparation method according to claim 3, characterized in that: The natural high molecular polymer in step (1) includes one or more of gelatin and collagen; the heat shrinkable material in the heat shrinkable material fiber membrane includes one or more of PU and PLGA; In the step (1), the mass ratio of the natural high molecular polymer to PCL is 3:1 to 1:3; The solvent in step (1) includes one or more of hexafluoroisopropanol, dichloromethane, tetrahydrofuran, and acetic acid; The thickness of the heat shrinkable fiber film in step (1) is 30 to 80 μm.

5. The preparation method according to claim 3, characterized in that: The mass percentage concentration of the spinning solution in step (1) is 5-20wt%; the electrospinning process parameters in step (1) include: spinning voltage of 10-20kV, receiving distance of 10-30cm, perfusion speed of 0.1-5mL / h, temperature of 10-30°C, and relative humidity of 20-70%; In the step (1), the heat-shrinkable material fiber membrane is a heat-shrinkable material electrostatic spinning membrane; The preparation of the heat-shrinkable material electrospinning membrane comprises: dissolving the heat-shrinkable material in a solvent to obtain a precursor spinning solution, and electrospinning to obtain a heat-shrinkable material fiber membrane.

6. The preparation method according to claim 3, characterized in that: In the step (1), the thickness of the high molecular polymer / PCL fiber membrane is 10 to 30 μm; and the thickness ratio of the natural high molecular polymer / PCL fiber membrane to the heat shrinkable material fiber membrane is 0.2 to 0.

8.

7. The preparation method according to claim 3, characterized in that: In the step (1), the heat-shrinkable material fiber membrane is used as a receiving device to directly receive and compound the high molecular polymer / PCL fiber membrane.

8. The preparation method according to claim 3, characterized in that: The heating cross-linking temperature in step (2) is 55-75°C, and the time is 15-60 minutes; the horizontal heat treatment temperature in step (2) is 15-45°C, and the time is 5-60 minutes.

9. The preparation method according to claim 3, characterized in that: The horizontal heat treatment in step (2) is performed by placing the device horizontally in hot water.

10. Use of the composite fiber material according to claim 1 in the field of medical dressings.